Acknowledgement to Reviewers of Pharmaceuticals in 2015 - Pharmaceuticals Editorial Office (MDPI AG, 2016)
The editors of Pharmaceuticals would like to express their sincere gratitude to the following reviewers for assessing manuscripts in 2015. [...]